2017
DOI: 10.1016/j.jacc.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Trends in U.S. Cardiovascular Care

Abstract: Cardiovascular disease is a leading cause of death and disability in the United States. National programs, such as the National Cardiovascular Data Registry, facilitate assessments of the quality of care and outcomes for broad populations of patients with cardiovascular disease. This report provides data for 2014 from 4 National Cardiovascular Data Registry hospital quality programs: 1) CathPCI (Diagnostic Catheterization and Percutaneous Coronary Intervention) for coronary angiography and percutaneous coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(101 citation statements)
references
References 22 publications
1
94
2
4
Order By: Relevance
“…Overall, the use of low-molecular-weight heparin was 65.2% in patients with NSTE-ACS in our study, which is much higher than the 10% in patients with NSTEMI reported by a contemporaneous study from the ACC National Cardiovascular Data Registries. 19 The major explanation for this discrepancy is likely that few patients underwent immediate invasive procedures in this study, 76.1% of patients undergoing PCI >24 hours after admission. Fondaparinux as anew anticoagulant medication has been considered as the first-line anticoagulant agent for conservative strategies in the ESC guideline recommendations (COR I, LOE B); however, the proportion of patients receiving fondaparinux was low in both patients with PCI or conservative treatment groups in this study.…”
Section: Downloaded Frommentioning
confidence: 77%
“…Overall, the use of low-molecular-weight heparin was 65.2% in patients with NSTE-ACS in our study, which is much higher than the 10% in patients with NSTEMI reported by a contemporaneous study from the ACC National Cardiovascular Data Registries. 19 The major explanation for this discrepancy is likely that few patients underwent immediate invasive procedures in this study, 76.1% of patients undergoing PCI >24 hours after admission. Fondaparinux as anew anticoagulant medication has been considered as the first-line anticoagulant agent for conservative strategies in the ESC guideline recommendations (COR I, LOE B); however, the proportion of patients receiving fondaparinux was low in both patients with PCI or conservative treatment groups in this study.…”
Section: Downloaded Frommentioning
confidence: 77%
“…This is essentially unchanged from the last analysis of national ICD implant practice in NZ in 2010 . The primary prevention ICD implant ratio reported in several international registries over the past decade is as follows: 46% in Denmark, 55% in Germany, 57% in the United Kingdom, 59% in Sweden, 62% in Spain, 63% in France, 73% in Canada, 75% in the United States, and 82% in Italy . The proportion of ICDs implanted in NZ for primary prevention indications is thus on the lower end of the range of contemporary international implant practice.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, high-dose statin treatment and other currently standard measures only prevent a fraction of recurrent events in survivors of myocardial infarction (MI) (1517). This residual burden of events presents a pressing unmet medical need.…”
Section: Inflammatory and Immune Mechanisms Participate In Atherothromentioning
confidence: 99%